Nurses' Knowledge and Practice Regarding Burn Wound Dressing in Sulaimaniyah, Iraq - Karim, Abubakr Sidiq Mohammed; Amen, Muhammad Rashid (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Burn is a public health issue, and the disinfected practice plays an important role in caring for patients with burns to reduce infection faster, recover, and maintain the status. Objectives: To assess nurses' knowledge and practice regarding burn wound dressing and utilizing aseptic techniques in dressing burn wounds. Patients and methods: The quantitative descriptive study using a non-probability convenience sample technique was used to recruit 45 nurses at Burn Plastic and Reconstructive Surgery Hospital, Sulaimaniyah, Iraq, from April to September 2022. A questionnaire was used to collect nurses' sociodemographic characteristics and their knowledge, while an observational checklist was used to evaluate their practice regarding burn wound management. Results: The mean age of participants was 40.8±6.7, most of whom were Nursing Institute graduates (86.7%). The mean score of experience as a nurse and in burn units were 16.1±5.6 and 14.8±4.9, respectively, and most of them (91.1%) had good knowledge regarding burn wound management. The proportion of satisfactory practice levels regarding preparation, procedure of burn wound dressing and general practice were 64.4%, 68.9%, and 66.7%, respectively. The proportion of regular introducing self, explaining the procedure, hand hygiene before the process, and documentation were zero. Conclusions: The nurses' knowledge of burn wound management was good, and most had satisfactory overall wound dressing practice. However, introducing themselves, explaining the procedure, hand washing, and documentation were the weakest aspects of the practice.
Keywords: Nurse knowledge; nurse practice; burn wound; dressing; quantitative descriptive study